2019
DOI: 10.1111/coin.12200
|View full text |Cite
|
Sign up to set email alerts
|

A novel hybrid credit scoring model based on ensemble feature selection and multilayer ensemble classification

Abstract: Credit scoring focuses on the development of empirical models to support the financial decision-making processes of financial institutions and credit industries. It makes use of applicants' historical data and statistical or machine learning techniques to assess the risk associated with an applicant. However, the historical data may consist of redundant and noisy features that affect the performance of credit scoring models. The main focus of this paper is to develop a hybrid model, combining feature selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…To solve this problem, more and more researchers have studied feature selection in recent years. Previous studies have shown that a single feature selection method cannot handle all classifiers and data sets well [ 32 ]. Although the existing studies have begun to focus on combining multiple feature selection methods to improve the performance of the classifier, there is a lack of interpretable optimal feature set determination method analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To solve this problem, more and more researchers have studied feature selection in recent years. Previous studies have shown that a single feature selection method cannot handle all classifiers and data sets well [ 32 ]. Although the existing studies have begun to focus on combining multiple feature selection methods to improve the performance of the classifier, there is a lack of interpretable optimal feature set determination method analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[28] found the problem of misclassifications near the optimal hyper plane by adopting SVM, accordingly provided an SVM-KNN Hybrid model with K-Nearest Neighbor (KNN) to cope with the defects, and validated this improved method on CRE. [29] proposed a three-phase hybrid credit prediction model, which contains preprocessing, ensemble feature selection and multilayer classifier framework. [30] presented a feature selection-based Hybrid-bagging algorithm (FS-HB) to assess credit risk, and obtained better performance compared with feature selection-based classifier and bagging.…”
Section: A Dbm-drbm Hybrid Modelmentioning
confidence: 99%
“…In the experiment, we used the Lending Club dataset. The official loan status of the dataset contains 6 categories, which is 'current' 'fully paid' 'late (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)' 'in grace period' 'late (31-120)' 'charged off'. For the purpose of this study, we considered loans issued of whole year of 2018, filtering out loans that are not fully paid or charged off yet.…”
Section: { }mentioning
confidence: 99%
“…This study introduces a novel procedure related to the model estimation and feature selection for ANNs in the context of credit scoring. Basically, this procedure is hybridized training of ANNs with a novel feature selection approach based on genetic algorithms (GAs) and information complexity criterion (ICOMP) 74‐77 …”
Section: Introductionmentioning
confidence: 99%